Optimasi Kelayakan Kondisi Pembangunan Jalan di Kota Lhokseumawe Menggunakan Algoritma Greedy - Eva Darnila; Mutammimul Ula; Cut Dewi Aida Soraya (JUKI : Jurnal Komputer dan Informatika, 2019)
Lhokseumawe City is one of the cities on the east coast of Aceh. The Lhokseumawe City area is the result of the expansion of the North Aceh region, where existing transportation facilities and infrastructure need to be optimized for development. Development is expected to improve the economy of the population around Lhokseumawe City, especially in the road construction sector. Considering the population growth in the Lhoseumawe City region which continues to increase every year, so that optimal road construction is expected to facilitate the mobility of the surrounding population in carrying out daily activities. To find out the condition of the existing roads around the city of Lhokseumawe in this study, the Indonesian Road Capacity Manual (MKJI) will be used to measure the degree of saturation of a road section in the Lhokseumawe City area. And the optimization is then used Greedy Algorithm, where this greedy algorithm is an optimization algorithm commonly used to solve optimization problems even though the results are not always optimal. The Greedy algorithm applied in this application will try to optimize by finding the nearest path from the Simpang Len road to Riyadhah Park by taking the coordinates (latitude and longitude) of the nodes to be passed. From the search results of the node that is depicted into graphs then it produces the optimal path that will be passed by the user is A → B → C → D → F → G → K → L → M → Q with a total distance of 9.8 km.